Medium Attribute of Geographical Environment in Geostrategic Intersection Area and Its Geo-Setting Effect—Taking Ukraine as an Example - Ye Shuai (Editorial Committee of Tropical Geography, 2021)
The relationship between the geographical environment and international politics is the main concern in geopolitical research. The existing publications were either inclined to environmental determinism, focused on the geographical imagination constructed by subjective discourse, or investigated the elements in the geographical environment as a whole to explore their interaction with politics. Evidently, discussion is lacking on how geo-entities use the spatial (structure) differentiation of geographical environments to act on power space and their geo-setting effects. Combining theoretical construction and case analysis, this study demonstrates the medium properties of geographical environment and its difference in efficiency of transmission power by proposing the concept of "geographical medium," and clarifies the geopolitical functions of different geographical mediums. Taking Ukraine as a case, the spatial practice of geo-entities mining is revealed herein; furthermore, the role of medium properties of the geographical environment in the enactment of power and their geo-setting effects are demonstrated. The results show that: (1) located in the geostrategic intersection zone, the geographical environment of Ukraine has a significant medium property, which provides a spatial intermediary for actors to establish power in Ukraine; (2) the geopolitical functions of various medium elements in Ukraine's geographical environment and their power transmission effectiveness to actors are significantly different. Geographical position and topography are geo-security functions. Natural resources have powerful geo-economic functions. Political parties and nationalities have strong geopolitical functions, while languages and religions have more prominent geocultural functions. The media attributes of natural resources, political parties, nationalities, and religions are strong; by contrast, the media attributes of geographical location and topography are gradually weakening; (3) different geo-entities (interest groups) compete to use the medium properties of the geographical environment to enact power, so that their geo-potential in Ukraine has alternating growth and decline, which intensifies turbulence in Ukraine's geo-setting. Finally, exploring the spatial practice and its effects of power exertion from the perspective of geographical media has enlightening significance for enhancing China's geopolitical influence abroad.